Factors influencing health worker compliance in implementing patient safety goals in Indonesia: Systematic review - Gani, Martinus Satya; Arso, Septo Pawelas; Dwiantoro, Luky (Indonesian Journal of Multidisciplinary Science, 2023)
The compliance rate of health workers in patient safety is not fully good at 68.7% and the implementation of patient safety in Indonesia is not optimal at 74.2% whereas in 2016 in Indonesia there were still 31 cases related to patient safety. To determine the factors that affect the compliance of health workers in the implementation of patient safety goals using a systematic review approach. This study uses a systematic review method from 9 studies using a quantitative approach commonly called a meta-analysis. The search for the source of this research data uses PRISMA flow charts from several databases such as Google Scholar, garuda portal, ProQuest, and Elsevier. Where published in the last 10 years (2013-2023). 25 variables were the same in the study between one researcher and another, namely age, gender, marital status, number of dependents, length of work, nurse knowledge, nurse motivation, supervision, nursing, organizational influence, educational status, compliance behavior, ability, supervisor support, fellow nurse support, workplace comfort, employment status, motivation, perception, nurse compliance, 6 patient safety goals, patient safety culture, patient identification, patient safety events, and patient fall prevention. The average P-Value value is 0.180, the minimum value of P-Value = 0.000, and the maximum value of P-Value = 0.995. 8 dominant factors influence health workers in implementing patient safety goals. 8 dominant factors influence health workers in implementing patient safety goals, namely knowledge, length of work, nurse work motivation, nurse perception, stress level and workload, nurse compliance, organizational influence, and supervisor support.